Field and laboratory methods in human milk research. Issue 1 (29th October 2012) - Miller, Elizabeth M.; Aiello, Marco O.; Fujita, Masako; Hinde, Katie; Milligan, Lauren; Quinn, E.A.
Abstract Human milk is a complex and variable fluid of increasing interest to human biologists who study nutrition and health. The collection and analysis of human milk poses many practical and ethical challenges to field workers, who must balance both appropriate methodology with the needs of participating mothers and infants and logistical challenges to collection and analysis. In this review, we address various collection methods, volume measurements, and ethical considerations and make recommendations for field researchers. We also review frequently used methods for the analysis of fat, protein, sugars/lactose, and specific biomarkers in human milk. Finally, we address new technologies in human milk research, the MIRIS Human Milk Analyzer and dried milk spots, which will improve the ability of human biologists and anthropologists to study human milk in field settings. Am. J. Hum. Biol., 2013. © 2012 Wiley Periodicals, Inc.